Carbon Nanowalls Synthesis and Emerging Applications - Hiramatsu, Mineo; Hori, Masaru; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2010)
Representing the first text to cover this exciting new area of research, this book will describe synthesis techniques of CNWs, their characterization and various expected applications using CNWs. Carbon-nanowalls (CNWs) can be described as two-dimensional graphite nanostructures with edges comprised of stacks of plane graphene sheets standing almost vertically on the substrate. These sheets form a wall structure with a high aspect ratio. The thickness of CNWs ranges from a few nm to a few tens of nm. The large surface area and sharp edges of CNWs may prove useful for a number of applications such as electrochemical devices, field electron emitters, storage materials for hydrogen gas, catalyst support. In particular, vertically standing CNWs with a high surface-to-volume ratio, serve as an ideal material for catalyst support for fuel cells and in gas storage materials.
Introduction: Discovery of two-dimensional carbon nanostructures;Characteristics of carbon nanowalls;Research on carbon nanowalls -- Preparation methods and growth mechanism:Microwave plasma enhanced chemical vapor deposition;Capacitively coupled plasma enhanced chemical vapor deposition with radical injection;Inductively coupled plasma enhanced chemical vapor deposition;Electron-beam-excited plasma enhanced chemical vapor deposition;Hot filament chemical vapor deposition;Atmospheric pressure plasma enhanced chemical vapor deposition;Sputtering;Discussion -- Physics of carbon nanowalls:Characterization of carbon nanowalls;SEM and TEM observation;Raman spectra of carbon nanowalls;Morphology control;Mechanical properties of carbon nanowalls;Field emission;Discussion -- Highly reliable growth process of carbon nanowalls using radical injection plasma-enhanced chemical vapor deposition:The idea of radical injection chemical vapor deposition;Radical density measurement in the plasma;Correlation between growth process and chamber wall conditions;Electrical conduction control of carbon nanowalls -- Applications:Carbon nanowall field emitters;Surface modification of carbon nanowalls;Electrochemical application of carbon nanowalls;Catalyst support for fuel cell application;Bio application of carbon nanowalls;Nanoimprint application -- Future directions.
Keywords: Chemistry, Organic; Chemistry; Catalysis; Mechanics; Production of electric energy or power; Nanotechnology; Materials Science; Nanotechnology; Power Electronics, Electrical Machines and Networks; Mechanics; Electrochemistry; Catalysis; Organic Chemistry